Exploration of the Concept of Wasat in the Qur'anic Worldview through Izutsu's Semantic Method - Ghifari, Muhammad Faiq Al; Rhain, Ainur; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
This paper aims to explore the meaning of the word wasaṭ and its various derivations in the Qur'ān. This word is closely related to an important theme that is highly relevant in people's lives, namely moderation. Moderation plays a key role in creating balance, harmony and tolerance at various levels, whether local, national or international. In order to comprehensively understand the concept of moderation, this study focuses on three main questions: what is the basic and relational meaning of the word wasaṭ, how has it developed historically, and how is the weltanschauung or worldview associated with the word wasaṭ reflected in the Qur'ān. This research is a literature study that collects data through the documentation method. The main sources used include the Qur'an, translations, tafsir, as well as various dictionaries to identify the meaning and derivation of the word wasaṭ. In the analysis, the author applies Toshihiko Izutsu's semantic theoretical framework, which includes three main aspects: (1) basic and relational meaning, (2) meaning in synchronic and diachronic contexts, and (3) weltanschauung or worldview related to the word. The basic meaning of the word و-س-ط is "middle". Relationally, through syntagmatic analysis, this word contains the meaning of justice, choice, excellence, best, and dominance, and refers to a just and superior figure. In paradigmatic analysis, the word wasaṭ has similar meanings with jānibun and qalbun, but contrasts with ḥaddun, shafā, ṭarafun, aṭrāfun, 'ażīmun, and karīmun.